De novo designed coiled coils as scaffolds for lanthanides, including novel imaging agents with a twist. Issue 56 (21st June 2021) - Webster, Alexandra M.; Peacock, Anna F. A.
Abstract : The design of artificial miniature lanthanide proteins, provide an opportunity to access new functional metalloproteins as well as insight into native lanthanide biochemistry. Abstract : For much of their history, lanthanides were thought to be biologically inert. However, the last decade has seen the discovery and development of the field of native lanthanide biochemistry. Lanthanides exhibit a variety of interesting photophysical properties from which many useful applications derive. The development of effective functional lanthanide complexes requires control of their coordination sphere; something proteins manage very effectively through their 3D metal-binding sites. α-Helical coiled coil peptides are miniature scaffolds which can be designed de novo and can retain the favourable properties of larger proteins within a much simplified system. Metal binding sites, including those which bind lanthanides can be engineered into the coiled coil sequence. This review will highlight the opportunities presented by the use of coiled coil peptides as scaffolds for lanthanide binding and the potential to control the coordination environment by simple modifications to peptide sequence. Designed lanthanide coiled coils offer opportunities to gain greater insight into native lanthanide biochemistry as well as to develop new functional complexes, including imaging agents.